Participation in the sustainability index and market value: evidence in open capital financial institutions (Revista Brasileira de Contabilidade e Gestão, 2020)
The purpose of this study is to investigate the influence that participation in corporate sustainability indexes had on the market value of publicly traded financial institutions, in the period from 2010 to 2015. The research sample includes 19 publicly traded financial institutions that are part of the Corporate Sustainability Index (ISE) and the Carbon Efficient Index (ICO2), of the Stock Exchange, Brazil and Branch [B] 3. The study is classified as descriptive, as for the procedures it is characterized as bibliographic and documentary and, in relation to the research problem approach, it is classified as quantitative. Due to the non-parametric behavior of the data, the Kruskal-Wallis test was adopted. The results of the statistical tests indicated that financial institutions listed on the ISE of [B] 3 show a significant increase in the return on shares as measured by the return on the daily quotations of companies. On the other hand, the participation of financial institutions in ICO2 does not provide a significant increase in the return on shares
Keywords: Financial Institution; Mean Test; Sustainability